Proposal for an organizational structure for the prevention of accidents in the mining sector - Carrillo Hidalgo, Norma (2012)
In our country, despite the eager of various enterprises and institutions related to mining concern to decrease accidents, this has not yet been possible, since statistics show that accidents still keep high rates. This present work seeks to focus the importance of organizational design in preventing accidents, since it is known every enterprise counts on various organizational designs according to their Chairmanship’s policy. There will therefore be various performances as for security. Several enterprises have been thus studied, making similarities between organizational design and accidents likely to happen, a good relation as for this aspect has been determined, and conclusions are that enterprises with a modern organizational design, where security is taken into due consideration, show low accident rates. On the contrary, traditionally-designed enterprises where security does not have a suitable hierarchical level show accidents high rates. For that reason new focus and organizational designs are required to contribute to decreasing accidents in our country.